Brain magnetic resonance imaging is a predictor of bimanual performance and executive function in children with unilateral cerebral palsy. (22nd January 2020) - Crichton, Alison; Ditchfield, Michael; Gwini, Stellamay; Wallen, Margaret; Thorley, Megan; Bracken, Jenny; Harvey, Adrienne; Elliott, Catherine; Novak, Iona; Hoare, Brian
Abstract : Aim: To examine the association between brain magnetic resonance imaging (MRI) characteristics and executive function and bimanual performance in children with unilateral cerebral palsy (CP). Method: Clinical MRI brain scans were classified as: (1) predominant pathological pattern (normal, white matter injury [WMI]; grey matter injury; focal vascular insults [FVI]; malformations; or miscellaneous); and (2) focal lesions (frontal, basal ganglia, and/or thalamus). Assessments included: (1) bimanual performance; (2) unimanual dexterity; and (3) executive function tasks (information processing, attention control, cognitive flexibility, and goal setting) and behavioural ratings (parent). Results: From 131 recruited children, 60 were ineligible for analysis, leaving 71 children (47 males, 24 females) in the final sample (mean age 9y [SD 2y], 6y–12y 8mo). Brain MRIs were WMI (69%) and FVI (31%); and frontal (59%), thalamic (45%), basal ganglia (37%), and basal ganglia plus thalamic (21%). Bimanual performance was lower in FVI versus WMI ( p <0.003), and with frontal ( p =0.36), basal ganglia ( p =0.032), and thalamic/basal ganglia lesions ( p =0.013). Other than information processing, executive function tasks were not associated with predominant pattern. Frontal lesions predicted attention control ( p =0.049) and cognitive flexibility ( p =0.009) but not goal setting, information processing, or behavioural ratings. Interpretation: Clinical brain MRI predicts cognitive and motor outcomes when focal lesions and predominate lesion patterns are considered. What this paper adds: Early brain magnetic resonance imaging (MRI) predicts bimanual performance and cognitive outcomes. Brain MRI may identify children requiring targeted interventions. Basal ganglia with/without thalamic lesions predicted bimanual performance. Frontal lesions were associated with attention control and cognitive flexibility. Brain MRI predominant patterns predicted motor, not cognitive outcomes, other than information processing. What this paper adds: Early brain magnetic resonance imaging (MRI) predicts bimanual performance and cognitive outcomes. Brain MRI may identify children requiring targeted interventions. Basal ganglia with/without thalamic lesions predicted bimanual performance. Frontal lesions were associated with attention control and cognitive flexibility. Brain MRI predominant patterns predicted motor, not cognitive outcomes, other than information processing. This article's abstract has been translated into Spanish and Portuguese. Follow the links from the abstract to view the translations. This article is commented on by Mankad on pages 546–547 of this issue. Resumen: La resonancia magnética cerebral es un predictor del rendimiento bimanual y la función ejecutiva en niños con parálisis cerebral unilateral Objetivo: Examinar la asociación entre las características de la resonancia magnética cerebral (RMN) y la función ejecutiva y el rendimiento bimanual en niños con parálisis cerebral unilateral (PC). Método: Los escáneres cerebrales de resonancia magnética clínica se clasificaron como: (1) patrón patológico predominante (normal, lesión de la sustancia blanca [WMI]; lesión de la materia gris; lesiones vasculares focales [FVI]; malformaciones; o varios); y (2) lesiones focales (ganglios frontales, basales y / o tálamo). Las evaluaciones incluyeron: (1) desempeño bimanual; (2) destreza unimanual; y (3) tareas de funciones ejecutivas (procesamiento de información, control de atención, flexibilidad cognitiva y fijación de objetivos) y calificaciones de comportamiento (padres). Resultados: De 131 niños reclutados, 60 no fueron elegibles para el análisis, dejando 71 niños (47 varones, 24 mujeres) en la muestra final (edad media 9 años [DE 2 años], 6 años ‐ 12 años 8 meses). Las RMN cerebrales fueron WMI (69%) y FVI (31%); y frontal (59%), talámico (45%), ganglios basales (37%) y ganglios basales más talámico (21%). El rendimiento bimanual fue menor en FVI versus WMI (p <0, 003), y con lesiones frontales (p = 0, 36), ganglios basales (p = 0, 032) y talámicas / ganglios basales (p = 0, 013). Aparte del procesamiento de la información, las tareas de la función ejecutiva no se asociaron con el patrón predominante. Las lesiones frontales predijeron el control de la atención (p = 0, 049) y la flexibilidad cognitiva (p = 0, 009) pero no el establecimiento de objetivos, el procesamiento de la información o las clasificaciones de comportamiento. Interpretación: La resonancia magnética cerebral clínica predice los resultados cognitivos y motores cuando se consideran las lesiones focales y los patrones de lesiones predominantes. Resumo: Imagem por ressonância magnética do cérebro como preditora do desempenho bimanual e função executiva de crianças com paralisia cerebral unilateral Objetivo: Examinar a associação entre as características do exame de imagem por ressonância magnética (IRM) e a função executiva e desempenho bimanual em crianças com paralisia cerebral (PC) unilateral. Método: Escaneamentos clínicos de IRM cerebrais foram classificados como: 1) padrão patológico predominante (normal, lesão da substância branca [LSB]; lesão da substância cinzenta; insultos vasculares focais [IVF]; malformações; ou outro); e (2) lesões focais (frontal, gânglios basais, e/ou tálamo). As avaliações incluíram: (1) desempenho bimanual; (2) destreza unimanual; e (3) tarefas de função executiva (processamento de informações, controle da atenção, flexibilidade cognitiva, e estabelecimento de metas) e pontuações comportamentais (pais). Resultados: De 131 crianças recrutadas, 60 eram inelegíveis para análise, restando 71 crianças (47 do sexo masculino, 24 do sexo feminino) na amostra final (média de idade 9a [DP 2a], 6a–12a 8m). IRMs cerebrais eram do tipo LSB (69%) e IVFs (31%); e frontais (59%), talâmicas (45%), de gânglios da base (37%), e de gânglios da base mais talâmicas (21%). O desempenho bimanual foi menor em IVF versus LSB ( p <0, 003), e com lesões frontais ( p =0, 36), gânglios da base ( p =0, 032), e talâmicas/gânglios da base ( p =0, 013). Com exceção do processamento de informações, as tarefas da função executiva não foram associadas com o padrão predominante. Lesões frontais foram preditivas do controle da atenção ( p =0, 049) e flexibilidade cognitiva ( p =, .009) mas não do estabelecimento de metas, processamento de informações, e pontuações comportamentais. Interpretação: A IRM cerebral clínica prediz resultados cognitivos e motores quando lesões focais e padrões predominantes de lesão são considerados.